ALTERNATIVE DONORS EXTEND TRANSPLANTATION FOR PATIENTS WITH LYMPHOMA WHO LACK AN HLA MATCHED DONOR - Bachanova, Veronika (Bone Marrow Transplant, 2014)
Alternative donor transplantation is increasingly used for high risk lymphoma patients. We analyzed 1593 transplant recipients (2000 to 2010) and compared transplant outcomes in recipients of 8/8 allele human leukocyte antigen (HLA)-A, -B, -C, and DRB1 matched unrelated donors (MUD; n=1176), 7/8 allele HLA-matched unrelated donors (MMUD; n=275) and umbilical cord blood donors (1 or 2 units UCB; n=142). Adjusted 3-year non-relapse mortality of MMUD (44%) was higher as compared to MUD (35%; p=0.004), but similar to UCB recipients (37%; p=0.19), although UCB had lower rates of neutrophil and platelet recovery compared to unrelated donor groups. With a median follow-up of 55 months, 3-year adjusted cumulative incidence of relapse was lower after MMUD compared with MUD (25% vs 33%, p=0.003) but similar between UCB and MUD (30% vs 33%; p=0.48). In multivariate analysis UCB recipients had lower risks of acute and chronic graft versus host disease compared with adult donor groups (UCB vs MUD: HR=0.68, p=0.05; HR=0.35; p<0.001). Adjusted 3-year overall survival was comparable (43% MUD, 37% MMUD and 41% UCB). Data highlight that patients with lymphoma have acceptable survival after alternative donor transplantation. MMUD and UCB can expand the curative potential of allotransplant to patients who lack suitable HLA-matched sibling or MUD.